Effect of Byrsonima crassa and Phenolic Constituents on Helicobacter pylori-Induced Neutrophils Oxidative Burst - Bonacorsi, Cibele [UNESP]; Raddi, Maria Stella Gonçalves [UNESP]; Fonseca, Luiz Marcos da [UNESP]; Sannomiya, Mirian; Vilegas, Wagner [UNESP] (Mdpi Ag, 2012)
Byrsonima crassa Niedenzu (Malpighiaceae) is used in Brazilian folk medicine for the treatment of diseases related mainly to gastric ulcers. In a previous study, our group described the gastric protective effect of the methanolic extract from the leaves of B. crassa. The present study was carried out to investigate the effects of methanolic extract and its phenolic compounds on the respiratory burst of neutrophils stimulated by H. pylori using a luminol-based chemiluminescence assay as well as their anti-H. pylori activity. The suppressive activity on oxidative burst of H. pylori-stimulated neutrophils was in the order of methyl gallate > (+)-catechin > methanol extract > quercetin 3-O-α-l-arabinopyranoside > quercetin 3-O-β-d-galactopyranoside > amentoflavone. Methyl gallate, compound that induced the highest suppressive activity with IC50 value of 3.4 μg/mL, did not show anti-H. pylori activity. B. crassa could be considered as a potential source of natural antioxidant in gastric ulcers by attenuating the effects on the damage to gastric mucosa caused by neutrophil generated reactive oxygen species, even when H. pylori displays its evasion mechanisms.
Keywords: Byrsonima crassa; Helicobacter pylori; Gastric ulcers; Antioxidant activity; Phenolic compounds; Chemiluminescence